Digitalisasi Pencatatan Keuangan melalui Pendampingan Aplikasi Money Tracker pada Toko Hawaii - Aisyah Fajriantini; Muhamad Amir Ariandi; Ulfah Nurfadhila; Vilianty Rafida (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2026)
This community service activity aims to improve financial literacy and the independence of the manager of Toko Hawaii Alat Jahit Samarinda in conducting digital business financial recording. The main problems faced by the partner include irregular and unstructured recording of income and expenses, as well as the potential mixing of personal and business finances. The activity was carried out using a participatory training approach through initial observation, interviews, financial management education, mentoring in the use of Money Tracker, transaction recording practice, and evaluation of the partner’s ability. Changes were measured using a structured observation sheet with indicators covering understanding of financial recording, income recording, expense recording, transaction categorization, separation of personal and business finances, and the ability to read financial summaries. The results show that the partner began to understand the importance of transaction recording as a basis for business control, started to develop the habit of recording income and expenses, and became more aware of the importance of separating business and personal finances. This activity indicates that MSME financial digitalization requires not only an application but also personal mentoring that can align technology with the partner’s habits and needs.